Evaluation of soil micronutrients under different spacing of Eucalyptus-based agroforestry system - BADESHRA, SANGAM; BHARDWAJ, K K; DEVI, SONIA; DAHIYA, GARIMA; DHILLON, R S (The Indian Journal of Agricultural Sciences, 2021)
A study was carried out during 2016–17 at Research Farm of the Department of Forestry, CCS Haryana Agricultural University, Hisar, Haryana to assess the effect of Eucalyptus planting geometry (17 m × 1 m × 1 m, 6 m × 1.5 m, 3 m × 3 m and devoid of trees, i.e. control) on soil micronutrients (zinc, iron, manganese, and copper) at the soil depths of 0–15, 15–30, 30-60 and 60–90 cm. The results showed that the different planting spacing of Eucalyptus, soil depths, and their interactions on micronutrients were significantly different and these were decreased with increasing the soil depth. The DTPA extractable micronutrient Zn, Fe, Mn, and Cu were in the range 0.8-1.3, 5.1-6.7, 6.8-8.1, and 2.6-3.1 mg/kg respectively. The soil micronutrient content decreased under a wider spacing agroforestry system but the maximum reduction was found under control treatment when compared with closer spacing (3 m × 3 m). The increase in micronutrient availability in soil due to the influence of Eucalyptus tereticornis was more in the surface (0-15 cm) than in subsurface soil (15-30, 30-60, and 60-90 cm) layers.